Pendampingan Pengembangan TPA Al-Hidayah melalui Penguatan SDM Pengajar di Desa Sawuh, Kec. Siman, Kab. Ponorogo - Alfarizi, Salman; Ashari, Riza; Wibowo, Hendri Setyo; Ansshori, Hamdan Fauzan; Sasongko, Yogi Banar (Journal Of Human And Education (JAHE), 2024)
Al-Qur'an education for children is an important foundation in forming a generation with noble morals and a strong understanding of religion. Al-Hidayah TPA in Sawuh Village, Siman District, Ponorogo Regency, is a non-formal educational institution that focuses on teaching the Koran and Islamic values. However, this TPA faces various challenges, such as less than optimal quality of teachers, lack of supporting facilities, and limited time and teaching focus. This community service program is designed to overcome these problems through an IPTEKS (Science, Technology and Arts) based approach. The steps taken include teaching methodology training, application of technology in learning, and regular assistance to increase teacher capacity. It is hoped that the results of this program will be able to improve the quality of education at TPA Al-Hidayah so that it can produce a young generation who are Quranic, have noble character, and are ready to face future challenges. Keywords: Al-Qur'an education, strengthening human resources, science and technology, community service